Explicating Shen Yun (神韵) in Chinese-to-English translation - a case study on chef Heman Tan's more than food affairs《餐桌上的大小事》 - Chan, Sou Tong (Nanyang Technological University, 2022)
Shen Yun (神韵, or literally Spirit-musicality) is the central piece of Chinese translation practice in the early 20th Century. Theoretical considerations on Shen Yun fade into oblivion as attention turns to western translation theories. This project sought to explicate Shen Yun in Chinese-to-English translation using a case study on Chef Heman Tan’s fifth book, More than Food Affairs (《餐桌上的大小事》), a biographical writing comprising two major text types, one emotional and idiosyncratic, and one instructional and cultural. While Shen Yun is said to be subjective and difficult to substantiate, the project proposed a few themes where translators could work on, including the image of the author and the stylistic and compositional elements of the ST. These themes are supported with appropriate illustrations to establish the contributing factors in reproducing a rendition endowed with the 'spirit' of the ST. Of particular interest is the fact that Heman, owing to his disability, is prevented from directly authoring his book titles. This presented a whole other dimension to capturing the author’s image and the style and compositional elements of the ST. Re-creation was introduced and crafted carefully with the author in mind. With these, it is hoped that the methods for Chinese-English translation could be further explored and documented, to balance the subjectivity of translator in achieving the spirit of Shen Yun in the TT.